Influence of storage temperature/time and atmosphere on survival and thermal inactivation of Escherichia coli ATCC 25922 inoculated to almond powder. (April 2018) - Cheng, Teng; Wang, Shaojin
Abstract: The purposes of this study were to explore combined effects of storage temperature, time and atmosphere on survival and thermal inactivation of pathogenic Salmonella Enteritidis PT 30 with nonpathogenic E. coli ATCC 25922 as a surrogate inoculated to low-moisture almond powder. A thermal death time test heating block system (TDT-HBS) was used to rapidly determine thermal inactivation of E. coli ATCC 25922. Surviving populations and D 75 -values of E. coli ATCC 25922 in the almond powder with 6.0% w.b. were determined monthly for 12-month storage under three packaging atmosphere conditions at −20, 4, and 24 °C. The results showed that survival and thermal inactivation curves of E. coli ATCC 25922 fitted well to both Weibull and first-order-kinetic models, respectively. The effects of storage atmosphere on reducing surviving populations and D 75 -values of E. coli ATCC 25922 became more remarkable as the storage temperature increased. The reductions of 2.55 log CFU/g for surviving populations and 31.2% for D 75 -values were observed after 12-months storage at 24 °C under modified atmosphere packaging (MAP), and holding for 50.4 min at 75 °C could reach at least 4-log reductions of E. coli ATCC 25922, which are required by the USDA for safe exportation. Storage under MAP at ambient temperature may hold potential to inhibit surviving populations and reduce thermal resistance of S. Enteritidis PT 30 in low-moisture almond powder. Highlights: Tolerance of E. coli was determined under 12-month storage at three temperatures. Inactivation of E. coli fitted well to both Weibull and first-order-kinetic models. D 75 -values of E. coli in almonds decreased with increasing stored temperature. The most favorable storage conditions of almonds were stored at 24 °C under MAP.